Node placement strategy in wireless sensor network - Ahmad, Puteri Azwa; Mahmuddin, Massudi; Omar, Mohd Hasbullah (IGI Global, 2013)
The performance and quality of services in wireless sensor networks (WSNs) depend on coverage and connectivity.Node placement is a fundamental issue closely related to the coverage and connectivity in sensor networks. Node placement influences the target position, coverage area, and connectivity in sensor networks.In random deployment, sensor nodes are deployed randomly in a non-invasive way.The deployment process may cause issues like coverage holes, overlapping, and connectivity failure.Enhancing coverage and connectivity are important for sensor networks to provide a reliable communication within sensing.Placing many sensor nodes in a WSN application region area is not the best solution due to cost and it results in multiple sensors used.Mobile sensor node is used as an alternative to overcome the random deployment problem.The virtual force based self node deployment is used in the mobility sensor to improve the coverage and connectivity area.Virtual Force Algorithm (VFA) approach using virtual repulsive and attractive forces is used to find the optimal node placement to minimize the problems. Simulation results proofed that a uniform deployment achieved using VFA approach with an optimal sensing range to cover the region of interest.